Ascorbic acid 6‐palmitate: a potent inhibitor of human and soybean lipoxygenase‐dependent lipid peroxidation. (22nd December 2013) - Mohamed, Riyaz; Tarannum, Shaista; Yariswamy, Manjunath; Vivek, Hamse K.; Siddesha, Jalahalli M.; Angaswamy, Nataraju; Vishwanath, Bannikuppe S.
Abstract Objectives Lipoxygenases (LOX) are the key enzymes involved in the biosynthesis of leukotrienes and reactive oxygen species, which are implicated in pathophysiology of inflammatory disorders. This study was conducted to evaluate the inhibitory effect of water‐soluble antioxidant ascorbic acid and its lipophilic derivative, ascorbic acid 6‐palmitate (Vcpal) on polymorphonuclear lymphocyte 5‐LOX and soybean 15‐LOX (sLOX) in vitro. Methods LOX activity was determined by measuring the end products, 5‐hydroperoxy eicosatetraenoic acid (5‐HETE) and lipid hydroperoxides, by spectrophotometric and high performance liquid chromatography methods. The substrate‐dependent enzyme kinetics and docking studies were carried out to understand the nature of inhibition. Key findings Vcpal potently inhibited 5‐LOX when compared with its inhibitory effect on sLOX (IC50; 2.5 and 10.3 μm respectively, P = 0.003). Further, Vcpal inhibited 5‐LOX more strongly than the known synthetic drugs: phenidone and nordihydroguaiaretic acid (P = 0.0007). Enzyme kinetic studies demonstrated Vcpal as a non‐competitive reversible inhibitor of 5‐LOX. In‐silico molecular docking revealed high MolDock and Rerank score for Vcpal than ascorbic acid, complementing in‐vitro results. Conclusion Both in‐vitro and docking studies demonstrated Vcpal but not ascorbic acid as a non‐competitive inhibitor of 5‐LOX‐ and sLOX‐induced lipid peroxidation, suggesting a key role for lipophilic nature in bringing about inhibition.